CAR-T therapy for neuroendocrine neoplasms: a review of molecular targets and clinical translation - Golounina, Olga; Minniakhmetov, Ildar; Khusainova, Rita; Loguinova, Marina; Salakhov, Ramil; Fan, Hui; Mokrysheva, Natalia (Frontiers in Immunology, 2025)
Neuroendocrine neoplasms (NENs) represent a heterogeneous group of malignancies. In metastatic and progressive forms, standard therapies are often ineffective. CAR-T therapy, which has demonstrated remarkable efficacy in hematologic malignancies, is considered a promising approach for NEN treatment, despite significant barriers inherent to solid tumors. This review aims to comprehensively analyze and systematize current scientific data on the development of CAR-T therapy for NENs of various origins. It focuses on relevant molecular targets, preclinical findings demonstrating the efficacy and safety profiles of CAR-T cells directed against potential targets, and the current status of early-phase (I/II) clinical trials for CAR-T therapy in NENs. The review examines major barriers to CAR-T therapy in solid tumors, including NENs, and presents innovative strategies to overcome them. Further research and clinical trials focusing on therapy personalization, enhanced safety and efficacy, and the development of combination approaches are essential for the successful integration of CAR-T therapy into clinical practice and for improving outcomes in patients with treatment-refractory NENs.